Application of gated conduits for fertigation in irrigation systems - Aydin, Alp Bugra; Tuna, Muhammed Cihat; Baylar, Ahmet (Iwa Publishing, 2022)
Fertigation involves dissolving fertilizer in irrigation water, and requires uniform water distribution and fertilization. A gated conduit can be used to inject liquid fertilizers or chemicals into a pressurized irrigation system. When the conduit gate is partially opened, a vacuum draws the fluid from the suction pipe into the conduit. An experimental study was conducted to investigate the fluid-injection ratio of gated conduits, which shown to be high. The density and viscosity of the fluid were the most important parameters affecting the fluid-injection ratio. That ratio increased with increasing Froude number. It decreased as the gate opening proportion increased and with increasing conduit length. A design formula related to the Froude number, and the fluid's density and viscosity is presented to enable estimation of the fluid-injection ratio.
Keywords: fertigation; gated conduit; injection; irrigation